Research progress on the PEGylation of therapeutic proteins and peptides (TPPs) - Li, Chunxiao; Li, Ting; Tian, Xinya; An, Wei; Wang, Zhenlong; Han, Bing; Tao, Hui; Wang, Jinquan; Wang, Xiumin (Frontiers in Pharmacology, 2024)
With the rapid advancement of genetic and protein engineering, proteins and peptides have emerged as promising drug molecules for therapeutic applications. Consequently, there has been a growing interest in the field of chemical modification technology to address challenges associated with their clinical use, including rapid clearance from circulation, immunogenicity, physical and chemical instabilities (such as aggregation, adsorption, deamination, clipping, oxidation, etc.), and enzymatic degradation. Polyethylene glycol (PEG) modification offers an effective solution to these issues due to its favorable properties. This review presents recent progress in the development and application of PEGylated therapeutic proteins and peptides (TPPs). For this purpose, firstly, the physical and chemical properties as well as classification of PEG and its derivatives are described. Subsequently, a detailed summary is provided on the main sites of PEGylated TPPs and the factors that influence their PEGylation.Furthermore, notable instances of PEG-modified TPPs (including antimicrobial peptides (AMPs), interferon, asparaginase and antibodies) are highlighted. Finally, we propose the chemical modification of TPPs with PEG, followed by an analysis of the current development status and future prospects of PEGylated TPPs. This work provides a comprehensive literature review in this promising field while facilitating researchers in utilizing PEG polymers to modified TPPs for disease treatment.